ADAPTASI DAN MITIGASI PETANI CABAI BESAR DI DESA SUMBEREJO DALAM MENGHADAPI PERUBAHAN IKLIM - Agadinansyah, Puput Regita; Suciati, Luh Putu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Climate change (C-C) causes erratic weather changes like today which have a negative impact on the agricultural sector, especially on seasonal crops such as horticulture, because it will inhibit plant growth and cause high growth of plant pest organisms. The phenomenon of climate change is a serious obstacle for actors in the agricultural sector, such as farmers. Therefore, this study aims to analyze farmers' perceptions, adaptation-mitigation actions taken, and analyze the factors that influence large chili farmers in adapting and mitigating climate change. The research location in the large chili center is in Sumberejo Village, Ambulu District, Jember Regency. The research method uses analytical descriptive with scoring analysis tools (Likert Scale and Guttman Scale) and logistic regression analysis. Determination of the sample that is as many as 32 farmers with disproportionate stratified random sampling method. The results showed that the majority of respondents had a moderate level of perception. The most frequently carried out climate change adaptation-mitigation actions are the use of high-yielding varieties and organic fertilizers, soil management and changes in cropping patterns with a high level of implementation, while significant factors that have the opportunity to increase the implementation of adaptation-mitigation are age variables, availability of information related to agriculture and climate change and pest attack frequency.